Eksperimen Pembelajaran Matematika dengan Strategi Discovery Learning dan Problem Based Introduction Terhadap Hasil Belajar Matematika Ditinjau dari Kedisiplinan Belajar Kelas VIII Semester Genap di SMP Muhammadiyah 4 Surakarta Tahun 2015/2016 - Agitanda, Mariska Merry; , Prof. Dr. Sutama, M.Pd (2016)
This study have three aims. (1) Test the effect discovery learning strategy and problem based introduction on learning outcomes in mathematics, (2) Test the effect learning discipline on learning outcomes in mathematics, (3) Test the interaction Discovery Learning and Problem Based Introduction and learning discipline on learning outcomes in mathematics. The research was conducted students of VIII Grade of SMP Muhammadiyah 4 Surakarta of even semester of academic year 2015/2016 with the population all students of VIII a number of 187 students. Type of the research is experiment with quasi experimental design. The class sample of research by using the strastified cluster random sampling. Experimental class has treated learning strategy discovery learning with steps: stimulation, problem statement, data collections, data processing, verification, dan generalization. While control class has treated learning strategy problem based introduction with steps: explain the purpose learning, motivate students, define and organize the task, gathering information, planning and preparing the work, and reflection. Methods of data collection use test, questionnaire, and documentation. Data analyzed by analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) There is effect discovery learning strategy and problem based introduction on learning outcomes in mathematics, (2) There is effects learning discipline on learning outcomes in mathematics, (3) There is no interaction discovery learning strategy and problem based introduction and learning discipline on learning outcomes in mathematics.